Veterinary vaccines principles and applications - Metwally, Samia; El Idrissi, Ahmed; Viljoen, Gerrit J. (Wiley-Blackwell, 2021)
"Veterinary Vaccines: Principles and Applications is a concise and authoritative reference on the use of vaccines against diseases of livestock. Compiled by Animal Health Officers at the UN-FAO and with contributions from international experts, the text comprises easily readable reviews of the latest research in vaccinology and vaccine immune response to pathogens of major economic impact to livestock"--